Creative, thus connected: The power of sociometric creativity on friendship formation in gifted adolescents—a longitudinal network analysis of gifted students - Hopp, Manuel; Zhang, Zhitian; Hinch, Leeanne; O’reilly, Colm; Ziegler, Albert (Special Issue:The Future of Research in Talent Development: Promising Trends, Evidence, and Implications of Innovative Scholarship for Policy and Practice, 2019)
The current study’s purpose is to explore the influence of peer-perceived creativity (sociometric creativity) on the short-term development of friendships during a summer program for high ability students. Specifically, the two main objectives of our study are: (1) How did students’ friendships network and sociometric creativity network evolve in the summer program? (2) How did sociometric creativity influence the friendship formation? The longitudinal study was conducted at the beginning, middle and the end of a 3-week long program for gifted students in Ireland. The sample consisted of Irish gifted students (N = 702, aged 13–18 years, 52% female, over thirty-one classes). Overall, our longitudinal multilevel and multigroup social network analysis shows that gifted adolescents formed reciprocated friendship ties and cohesive peer group structures in the investigated period; similar age and the same gender predicted friendship formation. Regarding the sociometric creativity, they tended to nominate a similar age and same gender student as very creative. Moreover, the sociometric creativity positively influenced adolescents’ friendship networks on a dyadic level, indicating that adolescents select friends based on their perception of the other student’s creativity. Further results, explanations, and implications are discussed.
CRIS-Team Scopus Importer:2019-11-29

From Implicit Theories to Creative Achievements: The Mediating Role of Creativity Motivation in the Relationship between Stereotypes, Growth Mindset, and Creative Achievement - Li, Pin; Zhang, Zhitian; Zhang, Yanna; Zhang, Jia; Nunez, Miguelina; Shi, Jiannong (Journal of Creative Behavior, 2020)
Research has demonstrated that implicit theories of creativity are crucial in shaping an individual’s behavior and real-life decisions toward being creative. The present study proposed and examined the underlying mechanisms of how two kinds of implicit theories—the growth mindset of the creative self and the stereotype of creative others—are associated with creative achievements through the mediating role of creativity motivation. Participants were 606 undergraduate students who were enrolled in an education major in two universities in China. Overall, the study found that Chinese students held a positive image toward a creative student, regarding him or her as highly competent, warm, and popular. Student perceptions of a creative other were positively related to their growth mindset of creativity. Moreover, results verified both the mediating role of creativity motivation on growth mindset, as well as the effect of positive stereotyping of the creative other on students’ creative achievement. These findings point to promising creativity motivation strategies including the cultivation of a malleable view of creativity and of creative role models, that may, in turn, promote creative achievement by encouraging students to do, learn, and accomplish new things.
CRIS-Team Scopus Importer:2020-04-21
Keywords: creative achievement; creativity motivation; growth mindset; stereotype

Social Environmental Factors and Personal Motivational Factors Associated with Creative Achievement: A Cross-Cultural Perspective - Zhang, Zhitian; Hoxha, Linda; Aljughaiman, Abdullah; Arenliu, Aliriza; Gomez-Arizaga, Maria P.; Gucyeter, Sule; Ponomareva, Irina; Shi, Jiannong; Irueste, Paula; Rogl, Silke; Nunez, Miguelina; Ziegler, Albert (Journal of Creative Behavior, 2020)
Although the theory of the socio-cultural approach to creativity is gaining steam, empirical studies with advanced statistical tools are lagging behind. To address the gap of empirical studies integrating individual, social environmental, and cultural factors, we examined how motivational factors and environmental responsiveness were jointly related to college students’ creative achievement in different nations. Participants were university students from eight culturally and geographically diverse regions: Argentina, Austria, Chile, China, Kosovo, Russia, Saudi Arabia, and Turkey. Overall, the results painted a generally positive picture of the relationship between environmental responsiveness, motivational factors, and creative achievement. By employing structural equation modeling (SEM) and multiple-group SEM (MGSEM) methods, results partially supported the mediation role of motivational factors between environmental responsiveness and creative achievement. In addition, we observed more consistent relationships between parental responsiveness and motivational factors or creative achievement, than lecturer. This held in common across all seven countries which fulfilled the requirements for the SEM process, indicating that parents play a potential vital role in supporting students’ motivational aspects and creative achievements, whereas lecturers supporting role is relative to the cultural organizational circumstances. As the first large-scale empirical study with a socio-cultural approach, we invited further discussion and proposed future cross-cultural research of this kind. Research implications and practical suggestions were addressed.
CRIS-Team Scopus Importer:2020-07-24
Keywords: creative achievement; creativity; lecturer responsiveness; motivational factors; parental responsiveness; socio-cultural approach

Social Perceptions of a Creative Person: Stereotypes and Prejudice of a Creative Student among German Adolescents - Zhang, Zhitian; Hopp, Manuel; Vialle, Wilma; Ziegler, Albert (Creativity Research Journal, 2020)
This study builds from the implicit theory of creative individuals to an understanding of the social perceptions of creative individuals. Stereotypes and prejudice about creative students were examined utilizing the self-developed stereotype and prejudice scales among German adolescents. The results indicate that German adolescents hold positive images of creative students, seeing them as competent, warm and popular. Their primary perception of a creative student was admiration, which could be predicted by their stereotypes. In addition, the gender and age effects on adolescents’ social perception were examined. The results show that boys and girls tend to expect the creative student to be the same gender as themselves; and the ratings of stereotype and prejudice in the pre-teens group were significantly higher than in the teens group. These findings provide a refined image of creative individuals from a social perception perspective and partially explain the observed variations due to gender and age factors.
CRIS-Team Scopus Importer:2020-10-30

The Relationships of Parental Responsiveness, Teaching Responsiveness, and Creativity: The Mediating Role of Creative Self-Efficacy - Zhang, Yanna; Li, Pin; Zhang, Zhitian; Zhang, Xingli; Shi, Jiannong (Frontiers in Psychology, 2022)
This study investigated the relationships between parental responsiveness, teaching responsiveness, and creativity, as well as the mechanism underlying these associations. We collected data from 584 Chinese college students via convenience sampling method and used self-report scales to measure their perceived parental responsiveness, teaching responsiveness, creative self-efficacy, and creativity. We employed structural equation modeling (SEM) to examine the relationships among these variables and the mediation effect. The results revealed that both parental responsiveness and teaching responsiveness were positively related to student creativity. Moreover, creative self-efficacy mediated the relationships of parental responsiveness, teaching responsiveness, and creativity. The findings highlight the significance of responsiveness from parents and teachers on student creativity and verify the potential mediating role of creative self-efficacy. These findings suggest that teachers and parents can foster creativity by providing warm and supportive responses to students' creative needs.
CRIS-Team WoS Importer:2022-03-11